(untitled) (CAHIERS MAGELLANES-NS, 2024)
Mauritius has ratified the Sustainable Development Goals Agenda, which makes a clear commitment to using the Fast-track method to end the AIDS pandemic by 2030. Further, Mauritius has made significant progress in the fight against AIDS, with the government establishing the National AIDS Secretariat in 2007, now governed by the Ministry of Health and Wellness. (2) The country's prevalence rate has remained under control at 1% over the past three years, with free services offered to all individuals and communities affected by HIV and AIDS. (3) In response to increasing competition and government changes, hospital organizations are focusing on their employees as a source of competitive advantage. (4) This shift towards Human Resource Management (HRM) involves implementing both "soft" and "hard" employee relations regulations to improve organizational performance. (5) Employee empowerment has emerged as a key strategy in promoting creativity and engagement among workers. Empowering employees in the service sector, particularly in hospitality, aims to enhance customer service quality and gain a competitive edge by enabling staff to provide exceptional customer experiences. (6) Ultimately, employee empowerment is seen as a valuable tool for improving organizational performance and customer satisfaction in the service industry. Challenges in hospital employee empowerment are evident in the Ministry of Health and Wellness's AIDS division, leading to high turnover, low productivity, and morale. The bureaucratic system hinders staff from expressing ideas, misuses authorities, and faces cooperation issues with other departments. Research on employee empowerment's impact is lacking.